Episiotomy preventing approaches among midwives in Kurdistan region - ahmed, hamdia (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: This study aimed to findout approaches which used by midwives for avoiding episiotomy and assess their knowledge regarding complications of episiotomy in three main cities of Kurdistan region. Methodology: A cross-sectional study was conducted between 1st January and 15th April 2014 in the three biggest maternity teaching hospitals. The study population included all the midwives (n=53) working in delivery rooms. Data were collected through interview with midwives. Results: The Midwives stated the followings as complications of episiotomy: tear into the rectum muscle or rectum itself (52.8%), bleeding (60.3%), infection and/or swelling of episiotomy area (62.2%), defect in wound closer (35.8%), local pain (32%). There was significant difference between knowledge of midwives in three cities regarding complications of episiotomy. Midwives used Good position, good vaginal support (35.8%), using Castor oil (32%), performing episiotomy only in indicated case (13.2%), no pushing without contraction (18.8%), giving enough time to mother (26.4%), using gel (15%), as episiotomy avoiding approaches. There was highly significant difference between three cities regarding episiotomy preventing approaches. Recommendations: training courses, developing guideline and establish clear and unified policy regarding episiotomy preventing approaches are necessary to decrease rate of episiotomy.